Seawater and sediment data from offshore wind farms in the German Bight collected during the cruise AT275 - Anna Ebeling; Ole Klein; Nathalie Voigt; Francisco de la Granda Grandoso; Simon Tewes; Torben Kirchgeorg; Ingo Weinberg; Daniel Pröfrock (PANGAEA, 2022)
Offshore wind energy is a steadily growing sector contributing to the worldwide energy production. The impact of these offshore constructions on the marine environment, however, remains unclear in many aspects. In fact, little is known about potential emissions from corrosion protection systems such as organic coatings or galvanic anodes composed of Al and Zn alloys, used to protect offshore structures. In order to assess potential chemical emissions from offshore wind farms and their impact on the marine environment water and sediment samples were taken in and around offshore wind farms of the German Bight between 06.03.2019 and 24.03.2019.